First Scientific Record for Sivas Aquatic Systems Related to Alien Fish Species:Small-scaled Pacu; Piaractus mesopotamicus (Teleostei:Characidae) - Bülent Ünver; Durdu Akdağ; Saniye Müzeyyen Vicdanlı (Turkish Journal of Agriculture: Food Science and Technology, 2021)
In July 2017, three specimens of an alien fish species were caught by the amateur fishermen in Kızılırmak River at Sivas city center. One of the fish specimens was taken from the fishermen for ichthyologic examination. The morphological, metric (23 features) and meristic characters (13 features) of this specimen were determined. The alien fish is with ovoid shape and flattened laterally. Mouth is in a sub-ventral position. The tooth row is double. Teeth formula are 3,2 / 2,3 (at first row on maxil) and 2 / 2 (at second row on maxil), 3,3 / 3,4 (at first row on mandibul), 1,1 (at second row on mandibul). The number of rakers on the first gill arch is 33. The scale numbers in line lateral are 107 (on right side) and 103 (on left side). The number of branched rays of dorsal, anal, pectoral, and ventral fins are 14, 24, 14, and 7; respectively. As a result of the evaluation of morphological, metric and meristic characters, it was decided that the alien fish caught from Kızılırmak was Piaractus mesopotamicus (Holmberg, 1887) belonging to the Characidae family. This species is also called as the small-scaled pacu. P. mesopotamicus is not among to native fish fauna of Kızılırmak. It is a fish species which originated from South America and is a tropical freshwater fish. These alien fish specimens which were caught by the amateur fishermen, probably translocated from a hobbyist aquarium to this aquatic system. Both directly and indirectly, invasive fishes affect a wide range of native organisms from zooplankton to mammals across multiple levels of biological organizations ranging from the genome to the ecosystem. This study is the first scientific record for Sivas aquatic systems related to alien fish species.